Nutritional Knowledge, Food Consumption, and Physical Activity in Relation to Nutritional Status among Students in Junior High School Muhammadiyah 9 Surabaya: A Descriptive Study - Lucyana Ahda Valeri; Mujayanto; Riezky Faisal Nugroho; Inne Soesanti (Journal of Nutrition Explorations, 2025)
Adolescence is a critical period marked by rapid growth and development, requiring optimal nutrition to support physical and cognitive functions. This descriptive quantitative study aimed to assess the relationship between nutritional knowledge, food intake, physical activity, and nutritional status among eighth-grade female students at SMP Muhammadiyah 9 Surabaya. Using total sampling, 48 students participated by completing structured questionnaires, 2×24-hour dietary recalls, and anthropometric measurements. Results showed that 97.9% of students had good nutritional knowledge. However, 56.3% had very low protein intake, 64.6% had very low fat intake, and 89.6% had very low carbohydrate intake, with no participants reaching normal carbohydrate consumption. Most students (52.1%) engaged in light physical activity. Despite poor dietary intake and low activity levels, 66.7% had normal nutritional status, while 26.0% were underweight, and 8.4% were overweight or obese. The findings reveal a disconnect between knowledge and behavior, suggesting that nutritional awareness alone does not ensure healthy practices. Environmental, economic, and behavioral factors likely influence this gap. The study highlights the importance of integrated interventions that address not only knowledge but also food access, habits, and lifestyle to improve adolescent health. A holistic, school-based approach is recommended to support adequate nutrition, physical activity, and growth during adolescence.